TUMOUR CASE IN KOI CARP (Cyprinus carpio) - Lili Sholichah; Angela Mariana Lusiastuti; Domenico Caruso; I Wayan Subamia; Uni Purwaningsih (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
A case study of tumour in koi carp (Cyprinus carpio) was observed in rearing periode. This tumour occurs solitary, large, pale red, fleshy masses under the lips and dental plates on the outside, and by reason of its size, may prevent closure the mouth. Moreover, this tumour goes through into the inside of the mouth. At necropsy, there were two soft, firm, small mass at inside of the mouth and the bigger mass at outside the mouth. Samples of this tumour were fixed in 10% formalin were used for histology analysis. The clinical course of the tumour is one of relatively slow but progressive growth. The proliferative stage of the neoplastic process is preceded and accompanied by a striking vascular reaction. Intensed hyperemia invariably occurs in that region of the mucosal surface which later becomes the site of neoplastic proliferation. Neoplastic cells lied around lamina propria and submucosal. These cells were joined together to make vacuolization and the other cells become pleiomorphism with hyperchromatic nucleus and N/C ratio cells are 1:1. In some area, there were many empty holes, around the holes there were debris cells, inflammation cells, and erythrocytes.